The seven-rayed scallop Pseudamussium peslutrae (Linnaeus, 1771) (Pectinidae) from the Rockall continental slope - Minchin Dan (Zenodo, 2023)
Pseudamussium peslutrae has a geographical range from southern Iceland and Norway southwards to the western Mediterranean Sea and North Africa. In this study, its biometrics were examined from two collections at mean depths of 353 and 517m from the Rockall continental slope, with only four scallops obtained at depths to 810m. Growth was based on the formation of shell rings, with one specimen having seventeen rings. Associates fouling the shells were classified according to nine taxa.